Opportunities and Challenges in Development of the Floating Solar Power Plant Project at the Adi Soemarmo Airport - Dhiyanti Nawang Palupi; Imam Supriyadi; Sri Sundari (CV. AFDIFAL MAJU BERKAH, 2024)
Electrical energy is the most critical need in the defense sector to maintain state sovereignty. The floating PLTS in Cengklik Reservoir can be used as the main electricity source in the Adi Soemarmo Air Base building to support energy security and avoid black outs. Cengklik Reservoir has a total surface area of ​​253 ha. This research aims to find out what opportunities and challenges there are in developing a floating solar power plant project at Adi Soemarmo Air Base so that it can reduce dependence on fossil energy as a primary energy source. The research method used is descriptive qualitative. The research results show that if the utilization of floating PLTS is assumed to be 5% by the Minister of PUPR's regulations, the area of ​​the Cengklik Reservoir where PLTS is installed is 12.65 ha, then a potential for floating PLTS of 14.80 MWp can be identified. This potential can support more reliable military operations. The challenge in building the floating PLTS project in Adi Soemarmo is that the distance between Cengklik Reservoir and Adi Soemarmo Air Base is 2.6 km, and regulations still need to be perfected in terms of permits.